Mediastinal lymphadenopathy: a practical approach. (3rd October 2021) - Iyer, Hariharan; Anand, Abhishek; Sryma, PB; Gupta, Kartik; Naranje, Priyanka; Damle, Nishikant; Mittal, Saurabh; Madan, Neha Kawatra; Mohan, Anant; Hadda, Vijay; Tiwari, Pawan; Guleria, Randeep; et al.
ABSTRACT: Introduction : Mediastinal lymphadenopathy is secondary to various benign and malignant etiologies. There is a variation in the underlying cause in different demographic settings. The initial clue to the presence of enlarged mediastinal lymph nodes is through thoracic imaging modalities. Malignancy (Lung cancer, lymphoma, and extrathoracic cancer) and granulomatous conditions (sarcoidosis and tuberculosis) are the most common causes. For a confident diagnosis, the clinician must choose from several available options and integrate the clinical, radiological, and pathology findings. An accurate diagnosis is necessary for optimal management. Areas covered : We performed a search of the PUBMED database to identify relevant articles on the causes, imaging modalities, and interventional modalities to diagnose these conditions. We discuss a practical approach toward the evaluation of a patient with mediastinal lymphadenopathy. Expert opinion : Mediastinal lymphadenopathy is a commonly encountered clinical problem. Treating physicians need to be aware of the clinico-radiological manifestations of the common diagnostic entities. Selecting an appropriate tissue diagnosis modality is crucial, with an intent to use the least invasive technique with good diagnostic yield. Endosonographic modalities (EBUS-TBNA, EUS-FNA, and EUS-B-FNA) have emerged as the cornerstone to most patients' diagnosis. An accurate diagnosis translates into favorable treatment outcomes.